[PP.01.26] PROTOCOL OF THE SWISS LONGITUDINAL COHORT STUDY (SWICOS) IN RURAL Switzerland. (September 2017) - Schoenenberger, A.; Muggli, F.; Suter, P.; Gallino, A.; Parati, G.; Ehret, G.; Schoenenberger-Berzins, R.; Resink, T.; Erne, P.
Abstract : Objective: Increased longevity and consequent major changes in demographics and population lifestyles necessitate new approaches to reduce the burden of aging-related diseases (including CVD) and maintain an optimal quality of life. This study aims to examine and longitudinally follow health status and disease risk factors in a Swiss rural cohort, evaluating all health related research and practice disciplines to assure development of new implementable and successful preventive strategies for healthy aging. Design and method: Small villages of rural regions in Switzerland with low migration rates have been selected for this longitudinal prospective study. All residents (age >=6 years, no upper age limit) are eligible. Target enrolment number per village is 300. Examinations and measurements encompass medical history, anthropometry, cardiac and vascular health, pulmonary function, physical performance, nutritional, mental and emotional status, biochemical and molecular analyses. Follow-up examinations (identical to baseline) will be performed after 5 and 10 years, and in 10-year intervals thereafter. Results: In the first participating village, more than 300 participants have been enrolled so far. Enrollment will start in a second participating village in 2017. Conclusions: This study will allow to: (1) identify "hidden" (asymptomatic and/or unrecognized) health problems which enhance risk for chronic diseases; (2) identify barriers to accessing health care and adapting health behaviours; (3) evaluate efficacy of present preventive strategies and recommendations; (4) evaluate knowledge and attitude towards ongoing health programs and public health recommendations; (5) monitor change and progress towards the national health objectives; (6) formulate new preventive strategies and recommendations based on the findings and knowledge base of the last 10 years; (7) formulate models for successful prevention of chronic diseases and for healthy aging.